When first language is not first: an functional magnetic resonance imaging investigation of the neural basis of diglossia in Arabic. (17th July 2014) - Nevat, Michael; Khateb, Asaid; Prior, Anat
Abstract In Arabic, the language used for everyday conversation ('spoken Arabic' – SA) differs markedly from literary Arabic (LA), which is used for written communication and formal functions. This fact raises questions regarding the cognitive status of the two varieties and their processing in the brain. Previous studies using auditory stimuli suggested that LA is processed by Arabic native speakers as a second language. The current study examined this issue in the visual modality. Functional magnetic resonance imaging (fMRI) responses were collected while Arabic–Hebrew bilinguals performed a semantic categorization task on visually presented words in LA, SA and Hebrew. Performance on LA was better than SA and Hebrew, which did not differ from each other. Activation in SA was stronger than in LA in left inferior frontal, precentral, parietal and occipito‐temporal regions, and stronger than in Hebrew in left precentral and parietal regions. Activation in SA was also less lateralized than activation for LA and Hebrew, which did not differ from each other in terms of lateralization, though activation for Hebrew was more extensive in both hemispheres than activation for LA. Altogether, these results indicate an advantage for LA in the current study, presumably due to participants' proficiency in reading in this language. Stronger activation for SA appears to be due to the relative unfamiliarity of written word forms in SA, which could also explain differences in performance between the two languages. However, the stronger activation observed in the left parietal cortex may also reflect stronger associations among words in SA.